The association among ball speed and the rotation of pivot leg, pelvis, and trunk separation in collegiate baseball pitchers - Naoki Wada; Mitsuo Otsuka; Yuta Yamaguchi; Takehiko Tsuji; Takatoshi Kojo; Tokuyoshi Kono; Tetsunari Nishiyama (Heliyon)
In baseball pitching, pivot leg is known to play an important role in linear acceleration down the mound. However, its contribution to the rotational movements of the proximal segments such as pelvis and upper body remains unknown. This study aimed to investigate the association between the pivot leg rotation, pelvis rotation, and trunk separation during the stride phase of baseball pitching in relation to ball speed. Three-dimensional kinematic data from 18 collegiate baseball pitchers were obtained during the maximal-effort pitches. The rotational angles and angular velocities of the pivot leg, pelvis, and upper trunk in the stride phase of pitching delivery were calculated to investigate the association of pivot leg rotation with pelvis rotation, upper trunk rotation, and trunk separation. The results showed that the rotational angular displacement of the pivot leg was positively correlated with pelvis rotation and negatively correlated with trunk separation during the stride phase and at the instant of stride foot contact. The peak rotation angular velocity of the pivot leg was also negatively correlated with trunk separation angle at stride foot contact. The trunk separation angle at the stride foot contact was the only variable that was positively correlated with ball speed. These results indicated that the pivot leg and pelvis behave similarly in terms of rotational movement in the transverse plane. Achieving greater trunk separation at stride foot contact, mainly by increasing pelvis rotation in association with pivot leg rotation, might increase ball speed. These findings can be useful when the coaches give instructions to modify the rotational mechanics of their pitchers.